CONFIRMING INDIANNESS THROUGH FOLKTALES: A STUDY INTO KARNAD'S HAYAVADANA - Saikia, Mompi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
In Girish Karnad's plays we discover indigenous subjects, myths, legends, history as well as folklore fused with Indian classical theatre technique and Indianised English language. His main purpose behind this is to revitalize Indian history and culture and, free it from Eurocentric domination as well as to confirm nationality in the field of Indian English drama. His dramatic technique of using Indian folktales, legends and history develops a kind of contemporaneity. This present paper is an attempt to explore the way Karnad has used folktales in his play Hayavadana (1971). The play has been taken as the primary data and the secondary data include articles from books, journals and magazines. The present study is based on a critical analysis and interpretation of the text.